2003
DOI: 10.1063/1.1559418
|View full text |Cite
|
Sign up to set email alerts
|

Removal of dangling bonds and surface states on silicon (001) with a monolayer of selenium

Abstract: Analysis of sub-stoichiometric hydrogenated silicon oxide films for surface passivation of crystalline silicon solar cells J. Appl. Phys. 112, 054905 (2012); 10.1063/1.4749415Thermal stability of ohmic contacts between Ti and Se-passivated n-type Si (001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 6 publications
0
32
1
Order By: Relevance
“…Further investigations are needed to clarify the detailed mechanism. As compared to the deposition of a Se monolayer between the metal and Si to change the SBH of the metal, [8][9][10] this method has several advantages. Selfaligned silicidation combined with S ion implantation can be easily used to fabricate nanometer MOSFETs.…”
Section: ͑ͻ10mentioning
confidence: 99%
See 2 more Smart Citations
“…Further investigations are needed to clarify the detailed mechanism. As compared to the deposition of a Se monolayer between the metal and Si to change the SBH of the metal, [8][9][10] this method has several advantages. Selfaligned silicidation combined with S ion implantation can be easily used to fabricate nanometer MOSFETs.…”
Section: ͑ͻ10mentioning
confidence: 99%
“…Pure metals, like Mg, Al, Cr, and Ti, on Se-passivated n-Si͑001͒ showed very low and even negative SBH values which can be predicted by the Schottky-Mott theory. [8][9][10] However, deposition of these elements seems inappropriate for silicide contacts on Si due to the suppression of silicide formation. 10 In order to benefit from advantages of silicides in state-of-art MOSFET technology, methods to tune the SBH of silicides on Si are required.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By terminating dangling bonds on the Si(100) surface, a low Schottky barrier close to 0 eV is expected between Al and n-type Si [11]. Figure 1 shows the I-V characteristics between two adjacent Al contacts on S-passivated n-type Si(100) surface at different temperatures.…”
Section: A Al/s-passivated N-type Si(100) Junctionsmentioning
confidence: 99%
“…Theoretical 5,6 and experimental [7][8][9] results showed that S or Se atoms are adsorbed in a bridge position on Si͑100͒. Tao et al 10,11 demonstrated that by passivating the Si͑100͒ surface with a monolayer of Se, the dangling bonds can be removed and nearly ideal Schottky barrier heights can be achieved using different metals. Use of a S or Secontaining solution is widespread for the passivation of the GaAs͑100͒ surface.…”
Section: Introductionmentioning
confidence: 99%